A Randomized, Double-Blind, Multicenter Clinical Study Comparing the Efficacy and Safety of a Drug Combination of Lopinavir/Ritonavir-Azithromycin, Lopinavir/Ritonavir-Doxycycline, and Azithromycin-Hydroxychloroquine for Patients Diagnosed with Mild to Moderate COVID-19 Infections - Purwati, - (Hindawi, 2021)
Background. At the present time, COVID-19 vaccines are at the testing stage, and an effective treatment for COVID-19 incorporating appropriate safety measures remains the most significant obstacle to be overcome. A strategic countermeasure is, therefore, urgently required. Aim. This study aims to evaluate the efficacy and safety of a combination of lopinavir/ritonavir-azithromycin, lopinavir/ritonavir-doxycycline, and azithromycin-hydroxychloroquine used to treat patients with mild to moderate COVID-19 infections. Setting and Design. This study was conducted at four different clinical study sites in Indonesia. The subjects gave informed consent for their participation and were confirmed as being COVID-19-positive by means of an RT-PCR test. The present study constituted a randomized, double-blind, and multicenter clinical study of patients diagnosed with mild to moderate COVID-19 infection. Materials and Methods. Six treatment groups participated in this study: a Control group administered with a 500 mg dose of azithromycin; Group A which received a 200/50 mg dose of lopinavir/ritonavir and 500 mg of azithromycin; Group B treated with a 200/50 mg dose of lopinavir/ritonavir and 200 mg of doxycycline; Group C administered with 200 mg of hydroxychloroquine and 500 mg of azithromycin; Group D which received a 400/100 mg dose of lopinavir/ritonavir and 500 mg of azithromycin; and Group E treated with a 400/100 mg dose of lopinavir/ritonavir and 200 mg of doxycycline. Results. 754 subjects participated in this study: 694 patients (92.4%) who presented mild symptoms and 57 patients (7.6%) classified as suffering from a moderate case of COVID-19. On the third day after treatment, 91.7%–99.2% of the subjects in Groups A–E were confirmed negative by a PCR swab test compared to 26.9% in the Control group. Observation of all groups which experienced a significant decrease in virus load between day 1 and day 7 was undertaken. Other markers, such as CRP and IL-6, were significantly lower in all treatment groups ( and ) than in the Control group. Furthermore, IL-10 and TNF-α levels were significantly elevated in all treatment groups (). The administration of azithromycin to the Control group increased CRP and IL-6 levels, while reduced IL-10 and TNF-α on day 7 () compared with day 1. Decreases in ALT and AST levels were observed in all groups (). There was an increase in creatinine in the serum level of the Control, C, D, and E groups (), whereas the BUN level was elevated in all groups (). Conclusions. The study findings suggest that the administration of lopinavir/ritonavir-doxycycline, lopinavir/ritonavir-azithromycin, and azithromycin-hydroxychloroquine as a dual drug combination produced a significantly rapid PCR conversion rate to negative in three-day treatment of mild to moderate COVID-19 cases. Further studies should involve observation of older patients with severe clinical symptoms in order to collate significant amounts of demographic data.